A Natural Science Museum as a Resource for Teaching and Learning - Rabanaque, Claudia (2021)
Nowadays, museums are conceived as places of educational value; they enable areas to promote learning related to specific topics, and they allow visitors to understand and interpret their environment, among other potentialities. This work presents the results of an experience carried out at the La Plata Museum (MLP) in which teachers and students of the Teaching Training Course in Natural Sciences participated through the Workshop ?Learning science between showcases, tablets and biological collections?. In this workshop, the participants were proposed to explore the potentialities of the strategies used in the MLP Exhibition Rooms, resorting to information and communication technologies, and approaching the Biological Collections, so that they can incorporate them into their teaching practices and respond to a survey. The workshop included four moments (start-Interactive area; Exhibition Hall; Biological collections; End-interactive area) with the aims of acquiring scientific skills, recognizing biological collections as valuable teaching resources, and promoting the importance of the teacher-museum relationship.